Brain Process for Perception of the “Out of the Body” Tactile Illusion for Virtual Object Interaction - Hye Jin Lee; Jaedong Lee; Chi Jung Kim; Gerard J. Kim; Eun-Soo Kim; Mincheol Whang (Sensors, 2015)
“Out of the body” tactile illusion refers to the phenomenon in which one can perceive tactility as if emanating from a location external to the body without any stimulator present there. Taking advantage of such a tactile illusion is one way to provide and realize richer interaction feedback without employing and placing actuators directly at all stimulation target points. However, to further explore its potential, it is important to better understand the underlying physiological and neural mechanism. As such, we measured the brain wave patterns during such tactile illusion and mapped out the corresponding brain activation areas. Participants were given stimulations at different levels with the intention to create veridical (i.e., non-illusory) and phantom sensations at different locations along an external hand-held virtual ruler. The experimental data and analysis indicate that both veridical and illusory sensations involve, among others, the parietal lobe, one of the most important components in the tactile information pathway. In addition, we found that as for the illusory sensation, there is an additional processing resulting in the delay for the ERP (event-related potential) and involvement by the limbic lobe. These point to regarding illusion as a memory and recognition task as a possible explanation. The present study demonstrated some basic understanding; how humans process “virtual” objects and the way associated tactile illusion is generated will be valuable for HCI (Human-Computer Interaction).